Blockchain Technological Transformation from a Centralized into a Decentralized Ecosystem: BlockCity Is Rising: N.A. - Hamzaee, Reza G (Archives of Business Research, 2022)
Blockchain technology has been considered more seriously in the 21st century than ever for some time till eventually it was flourished through evolution of IoT, or Internet of Things, and the first well defined cryptocurrency, namely Bitcoin. Unlike what most people link blockchain technology to cryptocurrency, blockchain technology is applicable to many businesses, commerce, insurance, banking, healthcare industry, etc., as well as cryptocurrency. Bitcoin’s extension into the 21st century’s monetary system was - and will continue to be - remembered as a historical turning point of the medium of exchange, store of value, and unit of account, among other desirable properties of money. The authors in this research paper, given their extensive exposure to both related research sources, activities, and MIT’s Intensive Executive Management Program on Blockchain Technology, and most importantly their recent partnership with 369 Smart Chain’s BlockCity, are incentivized to provide more clarity to the global community as to this rapidly emerging platform in the world. The authors have concluded that the blockchain technology is another revolution inside the capitalistic ecosystem for imposing its powerful forces in the conversion of centralized businesses into somewhat more decentralized, where competition and efficiency would be more established than otherwise. There will be more reliable information, permanently stored on electronic ledgers, connected to nodes merged with those already accessible through the blockchain platform, operated by entrepreneurs, such as BlockCity, just as an example.